Assessment of Sustainable Development Index for Thanh Hoa Province during Period from 2010 - 2014 - Tuan Lam, Manh (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Thanh Hoa is one of the fastest growing provinces in Vietnam and typical for strategic position in economy, society, national security and foreign affairs of the country. However, the socio-economic development is facing a range of challenges such as population growth, social inequality, environmental pollution and natural resource over-exploitation. In this paper, the establishment of sustainable development indicators (SIs) was implemented in order to measure the sustainability of Thanh Hoa province based on the analysis of the socio-economic characteristics and the sustainable development index (SDI). The proposed indicators framework consisted of five dimensions (economy, society, environment, infrastructure and governance), containing 33 indicators that potentially provided quantified methods for decision makers to examine better sustainability model and strategies in the current global and climate change scenario. Results showed that during the period from 2010 to 2014, Thanh Hoa province has generally developed to follow positive direction with continuously increasing the SDI scores over the years. In particular, the SDI in year 2014 (0.484) was much higher than that in comparison to year 2010 (0.136). Our results showed that these indicators can be potentially applied to other provinces of Vietnam to examine the sustainable development of whole country.